Implemantasi Fatwa MUI tentang Akad Mudharabah terhadap Produk Tabungan Safari Kospin Jasa Syariah Banjaran Tegal - Nurul Wulandari Putri; Dhiya Faras Febriani (Universitas Nahdlatul Ulama Surabaya, 2021)
economic system in everyday life. In the face of today's uncertain global economy, it is necessary for every individual to have a savings fund in life. Kospin Jasa Syariah Capem Banjaran is here to present various products that are needed by the wider community, one of which is the Safari Savings product. The purpose of this study is to determine the implementation of the application of the Fatwa DSN MUI on the Safari Savings product at Kospin Jasa Syariah Capem Banjaran. With descriptive qualitative method, the writer wants to know in detail the application of the fatwa in the field. The results of this study indicate that Kospin Jasa Syariah uses the mudharabah muthlaqah contract on the Safari Savings product, which is done in writing and the ratio is expressed as a percentage. However, in practice the safari savings product contains several points that are not in accordance with the fatwa DSN MUI, namely profits are not calculated clearly and Kospin Jasa Syariah sets the same nominal ratio until the end of the contract to customers.